2014
DOI: 10.1111/iej.12404
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of prevalence and characteristics of pre‐eruptive intracoronal resorption in unerupted teeth of the permanent dentition: a multicentre study

Abstract: Pre-eruptive intracoronal resorption defects occurred in 40 subjects. Increased awareness and careful radiographic examination of unerupted teeth may improve early detection and treatment of PIR defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
70
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(88 citation statements)
references
References 15 publications
9
70
3
1
Order By: Relevance
“…Treatments such as pulp protection or pulpectomy are performed in cases in which the pulp is affected. In the literature there are reports of rare cases in which the lesion progressed rapidly, and extraction of the tooth was indicated [1][2][4][5][6][7]10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatments such as pulp protection or pulpectomy are performed in cases in which the pulp is affected. In the literature there are reports of rare cases in which the lesion progressed rapidly, and extraction of the tooth was indicated [1][2][4][5][6][7]10 .…”
Section: Discussionmentioning
confidence: 99%
“…This lesion is generally localized on the occlusal, distal or mesial surfaces of the coronal portion, extending into various depths of dentin, rarely involves the pulp and preserves the healthy crown [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . It may be confused with caries, and mistakenly The best treatment option in this case was followup to minimize the risk of caries, and obtain stabilization of the lesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2] However, some studies suggested that PIR was associated with local factors, such as chronic apical inflammation and ectopic eruption, or systemic factors. [3][4] A number of case reports described this defect in permanent teeth, using panoramic or bitewing radiographs. 1-6-8 As conventional radiographs Cone Beam Computed Tomographic Analysis of Pre-Eruptive Intracoronal Resorption in a Primary Tooth: A Very Rare Case A AB BS S T TR RA AC CT T Pre-eruptive intracoronal resorption (PIR) is very rare in primary teeth, and the etiology and factors associated with the resorptive process remain unclear.…”
mentioning
confidence: 99%
“…7 Bu tarihten itibaren literatürde az da olsa olgu raporlarına rastlanırken, son yıllarda yapılan prevalans çalışmalarında %1,56-27,3 oranında bireyin etkilendiği ve %0,5-2,1 oranında dişte görülme sıklığı olduğu bildirilmiştir. 8,9 Bu lezyonların, genellikle klinik olarak asemptomatik olduklarından dolayı dişler sürmeden önce teşhis edilmelerinin yalnızca rutin kontrol seanslarındaki radyografik incelemeler sırasında gerçek-leştiği, bu nedenle erüpsiyona kadar sıklıkla fark edilmediği ve agresif çürük lezyonlarına dönüştüğü bildirilmiştir. 10,11 En çok etkilenen dişlerin sırasıyla alt 1. daimi molar, üst 1. daimi molar, alt 2. premolar ve alt 2. daimi molar dişler olduğu rapor edilmiştir.…”
unclassified